The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1111/j.1447-0756.2008.00745.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Evaluation of the effect of pentoxifylline on white blood cell count in serum and peritoneal fluid in female rats with endometriosis

Abstract: Based on our study, pentoxifylline could decrease the size of endometrial implants, especially in the ovaries and subcutaneous areas, and total white blood cell count in serum. Pentoxifylline could increase the lymphocyte count and decrease the neutrophil count in serum, and because these changes it might alter the immune system. Pentoxifylline did not have any adverse effect on rats' cycles and a good aspect of treatment with pentoxifylline was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Through the inhibition of phosphodiesterase in monocytes and macrophages, the drug suppresses cytokine production, mainly TNF-a in macrophages. Thus, it also has been used in the treatment of rheumatoid arthritis and inflammatory bowel disease (128,129). Based on the same indirect anti-TNF-a mechanism, this drug has been considered for the treatment of endometriosis.…”
Section: Pentoxifyllinementioning
confidence: 99%
See 1 more Smart Citation
“…Through the inhibition of phosphodiesterase in monocytes and macrophages, the drug suppresses cytokine production, mainly TNF-a in macrophages. Thus, it also has been used in the treatment of rheumatoid arthritis and inflammatory bowel disease (128,129). Based on the same indirect anti-TNF-a mechanism, this drug has been considered for the treatment of endometriosis.…”
Section: Pentoxifyllinementioning
confidence: 99%
“…In the rat model, implants of endometrial tissue in different locations (subcutaneous tissue, peritoneal surface, and ovarian area) were used to test the effect of pentoxifylline on lesions (128,129). Statistically significant reductions in the weight, volume, and number of lesions were documented (128,129).…”
Section: Pentoxifyllinementioning
confidence: 99%
“…Pa ral lel to the fin dings in the li te ra tu re, the gro up that rece i ved GnRHa tre at ment had sig ni fi cant re duc tions in the are as of the en do met ri o tic fo ci and ad he si on sco res com pa red to the rats in the con trol gro up. [5][6][7]21 Ho we ver, in ad di ti on to the high costs, it car ri es the risk of os te o po ro sis when used for long pe ri ods of ti me. Ad di ti o nally, GnRHa tre atment pro du ces se ve ral tro ub le so me si de ef fects beca u se of its strong an ti es tro ge nic ef fects, and re lap se might oc cur af ter the ces sa ti on of tre atment.…”
Section: Discussionmentioning
confidence: 99%
“…5 The tre at ment of en do metri o sis was in ves ti ga ted in ear li er stu di es with a rat mo del using GnRHa and go na dot ro pin re le a sing hor mo ne an ta go nists and va ri o us agents such as pen to xiphy lli ne, doxyc ycli ne, and le va mi zol. [5][6][7][8][9] GnRH ana lo gu es are be ing used ef fec ti vely in the tre at ment of en do met ri o sis and the re is a con sensus in the cur rent li te ra tu re that the se agents are ef fec ti ve. 5,9 The use of GnRHa with monthly injec ti ons or in jec ti ons with 3-month in ter vals in hibits ova ri an es tro gen synthe sis and forms a hypo es tro ge nic en vi ron ment, thus di mi nis hing the en do met ri o sis fo ci.…”
mentioning
confidence: 99%
“…Th e drug is known to suppress cytokine production, mainly TNF-α in macrophages which induces VEGF production 95 . In vitro animal models showed that the number, volume and weight of lessions were significantly reduced aft er PTX injection to endometriotic tissue 96 .…”
Section: Pentoxifylline (Ptx)mentioning
confidence: 99%